The impact of credit ratings on firms’ capital structure decisions in periods both with adverse and favorable credit market conditions - Karvounidis, Anastasios / AK (2017)
This study investigates the linked relationship between credit ratings and firms’ decisions regarding their capital structure. The content of this research is of great interest as the role of credit ratings has been vastly examined throughout the new millennium, while the capital structure of firms is considered to be one of the most well-researched topics in the field of corporate finance. Recent literature has focused thoroughly on the importance of the supply side factors which are potentially as prominent as the demand side factors in ascertaining corporate leverage. This very fact is based on the argument that firms with access solely in private debt markets do not necessarily have access in public debt markets as well, implying that the acquisition of a credit rating is the key factor that connects these two aspects. Moreover, some papers attempt to determine the influence of either actual or potential rating changes on managers’ decisions about the capital structure of their firms. However, the validity of these hypotheses was further explored on the onset of the financial crisis which agonized the markets from 2008 to 2010 because on that period their acceptability was quite questionable. Analyzing all these matters, it can be inferred that the credit rating-market access hypothesis (CR-MA) and the credit rating-capital structure hypothesis (CR-CS) have been depicted clearly by this research while the supply shock that afflicted negatively the non-financial firms has been captured from four different points of view and from two different sets of year-periods (i.e. 2001 to 2016, 2004 to 2011).